The government support and stakeholder engagement towards social entrepreneurship performance in Malaysia: an empirical investigation / Putri Aliah Mohd Hidzir, Shafinar Ismail and Erne Suzila Kassim - Mohd Hidzir, Putri Aliah; Ismail, Shafinar; Kassim, Erne Suzila (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Social entrepreneurship has been discovered and developed as a popular innovative method of eliminating or minimizing social issues. However, social enterprises in Malaysia face performance challenges and critical survival including financial sustainability and limited access to funding. In line with the government’s effort in certifying the status of social entrepreneurship through Social Enterprise Accreditation (SE. A), the research objective is to find out whether the government supports the stakeholder’s engagement contributing towards social entrepreneurship performance in Malaysia. A quantitative approach is used through the distribution of questionnaires among social enterprises in Malaysia as published by the Malaysian Global Innovation and Creativity Centre (MaGIC). The sampling procedure adopted in this research was purposive sampling. The results indicate that the government’s support and stakeholder’s engagement play important roles towards the performance of social entrepreneurship in Malaysia. The analyses presented in this research can be used by policymakers in terms of policymaking towards the growth and performance of social entrepreneurship in Malaysia. The findings achieved in this research will be of interest for practitioners and academicians concerned with the development of social entrepreneurship in Malaysia.